Risks factors associated with the development of Crohn's disease after ileal pouch-anal anastomosis for ulcerative colitis: a systematic review and meta-analysis - Fadel,MG; Geropoulos,G; Warren,OJ; Mills,SC; Tekkis,PP; Celentano,V; Kontovounisios,C (Journal of Crohn's and Colitis, 2023)
BackgroundFollowing ileal pouch–anal anastomosis [IPAA] for ulcerative colitis [UC], up to 16% of patients develop Crohn’s disease of the pouch [CDP], which is a major cause of pouch failure. This systematic review and meta-analysis aimed to identify preoperative characteristics and risk factors for CDP development following IPAA.MethodsA literature search of the MEDLINE, EMBASE, EMCare and CINAHL databases was performed for studies that reported data on predictive characteristics and outcomes of CDP development in patients who underwent IPAA for UC between January 1990 and August 2022. Meta-analysis was performed using random-effect models and between-study heterogeneity was assessed.ResultsSeven studies with 1274 patients were included: 767 patients with a normal pouch and 507 patients with CDP. Age at UC diagnosis (weighted mean difference [WMD] −2.85; 95% confidence interval [CI] −4.39 to −1.31; p=0.0003; I2 54%) and age at pouch surgery [WMD −3.17; 95% CI −5.27 to −1.07; p=0.003; I2 20%) were significantly lower in patients who developed CDP compared to a normal pouch. Family history of IBD was significantly associated with CDP (odds ratio [OR] 2.43; 95% CI 1.41–4.19; p=0.001; I2 31%], along with a history of smoking [OR 1.80; 95% CI 1.35–2.39; p<0.0001; I2 0%]. Other factors such as sex and primary sclerosing cholangitis were found not to increase the risk of CDP.ConclusionsAge at UC diagnosis and pouch surgery, family history of IBD and previous smoking have been identified as potential risk factors for CDP post-IPAA. This has important implications towards preoperative counselling, planning surgical management and evaluating prognosis.